BRACU BAT GPS based taxi fare meter - Hasan, Md. Toufiq; Mustafa, Benazir; Ahmed, Tanvir (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2016.